ANALISIS DU PONT SYSTEM UNTUK MENILAI KINERJA KEUANGAN SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BEI PERIODE 2020-2024 - Aulia Ika Febriani; Arif Hartono; Dwiati Marsiwi (Worksheet : Jurnal Akuntansi, 2026)
This study aims to assess the financial performance of plastic and packaging subsector companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The research method used is descriptive quantitative analysis using secondary data in the form of financial reports obtained from the website www.idx.co.id. The sample was selected using purposive sampling. The analysis technique used includes the du pont system analysis which includes the net profit margin ratio, total asset turnover, equity multiplier, return on investment, return on equity, with a time series and cross-section approach as well as a comparison with the industry average. The results of the analysis are used to identify the causes and impacts on the company. The results of the time series analysis using NPM tended to decrease by an average of 5.35% during the 2020-2024 period. Based on the TATO ratio, it tended to decrease by an average of 0.92 times. Based on the EM ratio, it tended to increase by an average of 1.52 times. Based on the ROI ratio, it tended to decrease by an average of 5.58%. Based on the ROE ratio, it tended to increase by an average of 7.89%. Meanwhile, the analysis of the results using a cross-sectional approach shows that the highest NPM was achieved by IMPC. The highest TATO was achieved by PBID. The highest EM was achieved by SMKL. The highest ROI was achieved by PBID. The highest ROE was achieved by PBID.